Effect of cobalt oxide on optical and dielectric properties of willemite-based glass-ceramics using white rice husk ash as silica source - Abdul Wahab, Siti Aisyah (2021)
Nowadays, researchers are interested in the production of willemite (Zn2SiO4) since it has good phosphor properties in optoelectronic applications. However, still lack of study in the fabrication of cobalt oxide (Co3O4) doped willemite based glass-ceramics (Zn2SiO4: Co2+) derive from white rice husk ash (WRHA). The Zn2SiO4: Co2+ were fabricated based empirical formula of (Co3O4)y[(ZnO)0.55(WRHA)0.45]1-y where y = 0.0, 0.1, 0.5, 1.0 wt.% heat-treated at 700-950 °C using melt-quenching technique. This research focuses on the effect of heat treatment and effect of Co3O4 doping on the physical, structural, optical, and dielectric properties of Zn2SiO4: Co2+ . The densities of undoped-Zn2SiO4 and Zn2SiO4: Co2+ increased from 3.4138 to 3.4659 g/cm3 as dopant increases, also the linear shrinkage increased from 6.23 to 6.92% when dopant increased. X-ray Diffraction (XRD) shows the formation of β−Zn2SiO4 at 750 ℃, then achieve stable state of α-Zn2SiO4 at 950 ℃. Meanwhile, the crystallite size was increased from 74.47 to 74.68 nm then decreased to 73.18 nm as dopant increased. Field Emission Scanning Electron Microscopy (FESEM) shows no obvious changes as the dopant increased. However, at 950 ℃, Zn2SiO4: 0.5 wt.% Co2+ and Zn2SiO4: 1.0 wt.% Co2+ showed a larger grain and less porosity compared to other samples. Fourier Transform Infrared (FTIR) spectroscopy showed eight significant vibrational bands of Zn2SiO4 at 750- 950 ℃ for both undoped and doped samples. The presence of SiO4 and ZnO4 bands in the FTIR absorption spectrum prove the formation of Zn2SiO4. The absorption spectra of UV-Visible were recorded in the range of 220-800 nm and the absorption band of undoped- Zn2SiO4 shifted to lower wavelengths (370 and 349 nm) at 900 and 950 ℃ respectively. When Co3O4 was introduced to Zn2SiO4 two absorption spectra occurred which is at 450 -700 nm and ~325 nm attributed to 4A2 → 4T1 ( 4P) transitions. The optical band gap was increased as dopants were introduced to Zn2SiO4 from ~4.09 eV to 4.57 eV then decreased to 4.29 eV. Photoluminescence spectroscopy (PL) showed blue emissions at ~420, ~444, ~464 and ~485 nm and green emission at ~525 nm under 325 nm excitation which attributed to the transition of Co2+ from 4A2 → 4T1( 4P). Besides, the dielectric constant increased from 4.84047 to 5.52423 when Co3O4 increase due to enhancement of the crystallinity and decrement of the polarization at higher temperatures. The dielectric loss remained low with the increase of dopant and AC conductivity showed each sample has different range of frequency cut-off which is at ~1.2, ~1.7, ~1.3 and ~1.4 GHz for undoped-Zn2SiO4, Zn2SiO4: Co2+ at 0.1, 0.5 and 1.0 wt.% respectively. The differences of frequency cut-off might occur due to the difference in ability of each sample to transport the electron when electric field is applied. In conclusion, the ability of the Zn2SiO4: Co2+ to exhibit blue emission and able to operate at higher frequency, also low loss makes it suitable to be used as a phosphor material in optoelectronic applications.